IoT-Based Rehabilitation Monitoring System for Carpal Tunnel Syndrome - Sidek, Mohammad Amir Asraf; Mohamed, Masnani (Evolution in Electrical and Electronic Engineering, 2022)
: Carpal Tunnel Syndrome is a typical disease that results in tingling and discomfort in the hand due to compression of the median nerve as it passes through the carpal tunnel, a tiny pathway on the palm side of the wrist. There are two ways to cure this syndrome which are surgery and rehabilitation. The current method used to cure this syndrome is the surgery method. This work is focusing on rehabilitation methods. IoT-Based Rehabilitation Monitoring System for Carpal Tunnel Syndrome is designed to monitor the measurement of bending angle during wrist flexion stretch exercise and measurement of grip force exaggerated on fingers. Patients can also check whether the exercises they have conducted are successful by referring to the measurement and alert shown. The main components used are the flexible bend sensor to measure the bending angle and force-sensitive-resistive (FSR) sensors to measure the grip force on fingers. ESP 32 is the microcontroller to controls the input and output of the system. The characteristics of the patient's bending angle and grip force were monitored using the Blynk application. The data is collected from 5 healthy subjects and one Carpal Tunnel patient. The collected data shows that there are improvements recorded from day 1 until day 4. 10.5% of improvement in the bending angle of the wrist is recorded. For the thumb finger, index finger, and middle finger, there are 6% improvements, 9% improvements, and 5.6% improvements respectively from the beginning of Day 1 until Day 4 in one week.